Holography for the very early universe and the classic puzzles of hot big bang cosmology - Nastase, Horatiu [UNESP]; Skenderis, Kostas (American Physical Society (APS), 2020)
We show that standard puzzles of hot big bang cosmology that motivated the introduction of cosmological inflation, such as the smoothness and horizon problem, the flatness problem, and the relic problem are also solved by holographic models for very early universe based on perturbative three dimensional QFT. In the holographic setup, cosmic evolution is mapped to inverse renormalization group (RG) flow of the dual QFT, and the resolution of the puzzles relies on properties of the RG flow.